Safety of gemtuzumab ozogamicin as monotherapy or combination therapy in an expanded-access protocol for patients with relapsed or refractory acute myeloid leukemia. Issue 8 (2nd July 2020) - Wang, Eunice S.; Aplenc, Richard; Chirnomas, Deborah; Dugan, Michael; Fazal, Salman; Iyer, Swaminathan; Lin, Tara L.; Nand, Sucha; Pierce, Kristen J.; Shami, Paul J.; Vermette, Jennifer J.; Abboud, Camille N.
Abstract: Gemtuzumab ozogamicin (GO) remained available to US clinicians through an open-label expanded-access protocol (NCT02312037) until GO was reapproved. Patients were aged ≥3 months with relapsed/refractory (R/R) acute myeloid leukemia (AML), high-risk myelodysplastic syndrome, or acute promyelocytic leukemia (APL), and had exhausted other treatment options. Three hundred and thirty one patients received GO as monotherapy for R/R AML ( n = 139), combination therapy for R/R AML ( n = 183), or treatment for R/R APL ( n = 9). Corresponding treatment discontinuations occurred in 68, 39, and 33% of patients. All-causality grade 5 AEs occurred in 52, 22, and 22% of patients in the monotherapy, combination, and APL groups, respectively. Corresponding grades 3 and 4 treatment-related AEs were reported in 60, 55 and 78% of patients. Hepatotoxicity occurred in five patients: veno-occlusive disease ( n = 4) and drug-induced liver injury ( n = 1). GO was generally well tolerated in patients with R/R AML or APL. Most frequent treatment-related grade ≥3 AEs were hematologic AEs. Clinicaltrials.gov identifier: NCT02312037